2011
DOI: 10.1177/0194599811413373
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Low‐Cost Sinus Surgery Task Trainer

Abstract: Sinus surgery simulation has proven to be a valuable teaching tool, yet the cost of many simulators limits the incorporation of this technology into training programs. The authors developed an inexpensive endoscopic sinus surgery task trainer and evaluated its value as a means of developing basic endoscopy and sinus surgery skills. For less than 5 US dollars, the training model was constructed using gelatin and embedded with reusable, recyclable, and readily available materials. Ten attending otolaryngologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 10 publications
1
63
0
1
Order By: Relevance
“…23 Face, content, and construct validity have all been established by using this model, although it is moderately time intensive to build. 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…23 Face, content, and construct validity have all been established by using this model, although it is moderately time intensive to build. 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…The material characterisation of ballistic gelatin presented here can find application in in situ studies that employ the material in physical phantoms (such as of breast, liver or brain) for surgical training (Malekzadeh et al (2011)) or evaluation of traumatic brain injuries, and in in silico studies investigating computational models of such processes (Chafi et al (2010)). The constitutive model and optimised material parameter values indicate that ballistic gelatin has similar properties to soft tissues in general, which is encouraging for its use as a soft tissue simulant.…”
Section: Discussionmentioning
confidence: 99%
“…composition and shape), and ethical implications. Ballistic gelatin in particular has frequently been employed as a soft tissue substitute (Kwartowitz (2012); Malekzadeh et al (2011);Mendez-Probst et al (2010)) as it is biologically-derived and has favourable properties such as biodegradability and ease of manufacture and preparation. Moreover, its mechanical properties and response to a variety of mechanical tests have been found to be similar to those of soft tissues (Breeze et al (2013); Kalcioglu et al (2010)), further enhancing its suitability as a substitute.…”
Section: Introductionmentioning
confidence: 99%
“…This was because the learning process was considered to be more important than the physical substrate [18]. The Georgetown low-cost sinus trainer costs $5 and allows the trainee to practise basic endoscopy and sinus surgery skills including recess probing, targeted injections, removal of a suture, removal of a foreign body and antrostomy creation using an egg [19,20] University of Toronto developed a low-cost, low-idelity, easily constructed simulator for $20 with ive diferent training modules and demonstrated that training on the model had a positive impact on ESS skills [21,22]. More recently, the University of Texas [23] have produced a silicone injection moulded ESS simulation model at low cost and testing revealed high ratings for both face and construct validity.…”
Section: Simulationmentioning
confidence: 99%